RANCANG BANGUN ALAT UKUR KUALITAS TANAH UNTUK REKOMENDASI TANAMAN BERBASIS MIKROKONTROLER - Anggraini, Yuni; Ferdian, Rian; Yendri, Dodon (Universitas Andalas, 2024)
Indonesia is known as an agrarian country which is very suitable as a farming area. In farming, of course, many factors affect the growth and development of planted plants. One of the factors that influence this is soil quality. Therefore, research was conducted to make design a soil quality measuring instrument for microcontroller-based plant recommendations. The purpose of this design is that the system can measure soil quality and send measurement information and recommend plants that are suitable for planting on a particular land through the Android application. This soil quality measuring device uses an ESP32 microcontroller equipped with Wifi, a DS18B20 sensor, a Soil Moisture sensor, and a soil pH sensor. The system performs input processing using the Tsukamoto fuzzy logic method. Where the results obtained in this design test are the system can send the results of soil quality measurements and recommendations for suitable plants to be planted then can send measurement information and recommendations through the Android application. So it can be concluded that the soil quality measurement tool for recommending plants can work well and has fulfilled the purpose of making this tool.